The Potential of Gamification to Improve Employee Onboarding - Utegenova, Alisha; Hořáková, Marie; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor’s thesis studies how gamification might improve the onboarding process of the chosen company. Traditional onboarding may result in poor knowledge retention and information overload, leading employees to feel overwhelmed and have lower motivation. These problems were addressed using a mixed-methods approach, including prototype testing, semi-structured interviews, and surveys. The study analysed the existing onboarding process, then developed a gamified prototype called “Onboarding Quest,” and tested it with new hires. Results showed that gamified features, such as levels, badges, progress tracking, and interactive tasks, increased engagement, motivation, and user satisfaction. Participants appreciated the structure and interactivity of the new system and reported better short-term knowledge retention. Although the prototype had limitations in scope and budget, the findings suggest that gamification holds strong potential for making onboarding more effective, mainly when supported by motivational theories like Self-Determination Theory and Flow Theory. Further research with a bigger and diverse sample is needed to validate these findings in real-world conditions.
Vedoucí práce: Marie Hořáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses